THE ANALYSIS OF PRODUCTIVE ZAKAT UTILIZATION STRATEGY (CASE STUDY OF LAZ NURUL HAYAT) - Nico Stenly Yoshua; Tika Widiastuti (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This study aims to analyze the strategy of utilizing productive zakat in the Zakat Institution of Nurul Hayat. Every zakat institution needs an appropriate and efficient strategy in managing zakat funds so that every mustahiq can be transformed into muzakki. This study uses a qualitative approach with case study research methods. The technique of collecting data uses direct interviews, documentation and observation. To analyze the data, this paper uses the SWOT Matrix and then uses QSPM to identify a new strategy. Then to find out the validity of the data, researchers used triangulation techniques by matching the findings of primary data and secondary data. The results obtained that through the SWOT analysis obtained four strategies and through the QSPM analysis the following results are obtained: SO strategy, namely the expansion of the program in collaboration with Dukcapil/Depkop to reach mustahiq who are entitled to power through zakat has a score of 3,735; WO's strategy is to form an R&D division with a score of 6.085; The ST strategy of introducing digital e-commerce technology to Mustahiq has a score of 6.085; The WT strategy of selecting mustahiq has a score of 2.715 Keywords: LAZ, Zakat, SWOT, QSPMREFFERENCE Adi Isbandi Rukminto. (2002). Pemikiran-pemikiran dalam Pembangunan Kesejahteraan Sosial. Jakarta: Lembaga Penerbit FE-UI.Asnaini. (2008). Zakat produktif dalam perspektif hukum Islam. Yogyakarta: Pustaka Pelajar.Fred R. David. (2015). Manajemen strategi, edisi bahasa indonesia, edisi 15. Jakarta: PT Indeks Kelompok Gramedia.Indriantoro, Nur dan Bambang Supomo. (2002). Metodologi penelitian bisnis. Yogyakarta: BPFE.Khasanah, Umrotul. (2010). Manajemen zakat modern. Malang: UIN Maliki Press.Nastiti, Novalia dan Imron Mawardi. (2014). Kemampuan unit usaha LAZ Nurul Hayat dalam menunjang biaya operasional lembaga amil zakat. Jurnal Ekonomi Syariah Teori dan Terapan, 1(2), 92-118.Pusat Kajian Strategis Badan Amil Zakat Nasional (PUSKAS BAZNAS). (2018). Outlook zakat Indonesia 2018. Jakarta: Pusat Kajian Strategis BAZNAS.Qur’an in Word Ver 1.3 created by Mohammad Taufiq. Rasjid, Sulaiman. (1954). Fiqh sunah, cet. Ke-17. Jakarta: Attahariyah.Soemitra, Andri. (2009). Bank dan lembaga keuangan syari’ah. Jakarta: Kencana.Sugiyono. (2013). Metode penelitian pendidikan pendekatan kuantitatif, kualitatif, dan R&D. Bandung: Alfabeta.Sudirman. (2007). Zakat dalam pusaran arus moderenitas. Malang: UIN-Malang Press.Uha, Nawawi, Ismail. (2013). Manajemen zakat dan wakaf. Jakarta: VIV Press.Widiastuti, Tika dan Suherman Rosyidi. (2015). Model pendayagunaan zakat produktif oleh lembaga zakat dalam meningkatkan pendapatan mustahiq. Jurnal Ekonomi dan Bisnis Islam, 1(1), 89-102.William F. Glueck and Lawrence R. Jaunch. (1990). Manajemen strategis dan kebijaksanaan perusahaan. Jakarta: Erlangga.